Internalisasi Budaya Siri’ Na Pacce dalam Minimalisir Normalisasi Catcalling di Kalangan Remaja Wanita di Kota Surabaya - Rizqi, M. Yusuf; Fajriani, Himma; Ma’diro, Maslakhatul; Ramadhan, Irsyadulloh (IAI Nasional Laa Roiba Bogor, 2024)
Catcalling is a form of verbal sexual harassment in the form of an exclamation or comment made by someone to attract the victim's attention that contains sexual elements. The rise of catcalling on teenage girls in Surabaya City is certainly a concern because of the impact caused by catcalling. Gender inequality and patriarchal culture are also factors in catcalling. Siri' na Pacce is a philosophy of life for the Bugis-Makassar people that is still upheld today. Siri' na Pacce as a solution offer for people in Surabaya City because the value contained in it can minimize catcalling in Surabaya. The problems posed in this research are first, how the Surabaya city community views the normalization of catcalling; second, whether the essence contained in Siri' na Pacce can minimize catcalling in Surabaya City. The purpose of writing this article is to find out how effective Siri' na Pacce is as a form of minimizing female teenage catcaliling in Surabaya City. The research method used in the research is a mix method, namely qualitative and quantitative. Quantitative to understand the views of the Surabaya community regarding the catcalling phenomenon. While qualitative to explore information related to siri' na Pacce. The research concluded that the essence contained in siri' na pacce can be applied in Surabaya City to prevent catcalling through education and behavioral examples that reflect the figure of an ethical individual.